Orthostatic Hypotension in Patients with Parkinson’s Disease and Atypical Parkinsonism - Seyed-Mohammad Fereshtehnejad; Johan Lökk (Parkinson's Disease)
Orthostatic hypotension (OH) is one of the commonly occurring nonmotor symptoms in patients with idiopathic Parkinson’s disease (IPD) and atypical parkinsonism (AP). We aimed to review current evidences on epidemiology, diagnosis, treatment, and prognosis of OH in patients with IPD and AP. Major electronic medical databases were assessed including PubMed/MEDLINE and Embase up to February 2013. English-written original or review articles with keywords such as “Parkinson’s disease,” “atypical parkinsonism,” and “orthostatic hypotension” were searched for relevant evidences. We addressed different issues such as OH definition, epidemiologic characteristics, pathophysiology, testing and diagnosis, risk factors for symptomatic OH, OH as an early sign of IPD, prognosis, and treatment options of OH in parkinsonian syndromes. Symptomatic OH is present in up to 30% of IPD, 80% of multiple system atrophy (MSA), and 27% of other AP patients. OH may herald the onset of PD before cardinal motor symptoms and our review emphasises the importance of its timely diagnosis (even as one preclinical marker) and multifactorial treatment, starting with patient education and lifestyle approach. Advancing age, male sex, disease severity, and duration and subtype of motor symptoms are predisposing factors. OH increases the risk of falls, which affects the quality of life in PD patients.